Indirect electrochemical degradation of acetaminophen: process performance, pollutant transformation, and matrix effects evaluation - Efraím A. Serna-Galvis; Ricardo E. Palma-Goyes; Ricardo Antonio Torres-Palma; Juan Esteban Ramírez (Revista Facultad de Ingeniería Universidad de Antioquia, 2021)
Acetaminophen (ACE), a highly consumed pharmaceutical, was degraded in aqueous matrices by reactive chlorine species (RCS) electrogenerated using Ti/IrO2 electrodes. Although this pollutant has been extensively treated by electrochemical techniques, little information is known about its degradation in fresh urine by electrogenerated RCS, and the understanding of its transformations using analyses of atomic charge. In this work, these two topics were discussed. Initially, the effect of current (10-40 mA) and supporting electrolyte (considering typical ions present in surface water and urine (Cl- and SO42-)) on the electrochemical system was evaluated. Then, the kinetics and primary transformations products involved in the elimination of ACE were described. It was found that, in distilled water, the process at 40 mA in NaCl presence led to 100 % of ACE degradation (10 min, 0.056 Ah L-1). Theoretical analyses of atomic charge for ACE indicated that the amide group is the most susceptible to attacks by RCS such as HOCl. On the other hand, degradation of acetaminophen in synthetic fresh urine was slower (21% of degradation after 60 min of treatment) than in distilled water. This was attributed to the other substances in the urine matrix, which induce competition for the degrading RCS.